Genetic variation within and between an isolated population of Phyteuma spicatum L. ssp. coeruleum R. Schulz near Mrągowo (northeastern Poland) and populations of P. spicatum L. ssp. spicatum - Sawicki, Jakub; Szczecińska, Monika; Korniak, Tadeusz; Hołdyński, Czesław (Biodiversity: Research and Conservation, 2006)
The aim of this study was to determine genetic variation within populations of two Phyteuma spicatum subspecies, and to estimate genetic differences between them. An analysis of 5 enzyme systems, i.e. AAT, EST, GDH, MDH and LAP, revealed 11 loci for ssp. coeruleum and 10 for ssp. spicatum. Four RAPD markers revealed 25 loci. The population of P. spicatum ssp. coeruleum examined in the study was found to be genetically variable, and the level of its variation did not differ from that estimated for the typical subspecies. Genetic similarity was very high between the two populations of the typical subspecies but low between any of them and the population of P. spicatum ssp. coeruleum. Some of the isoenzymatic and DNA markers enable identification of both taxa.